ANALISIS IMPLEMENTASI AKAD PEMBIAYAAN MUDHARABAH DI KJKS ARTHA BUANA PERSPEKTIF HUKUM EKONOMI SYARIAH - Moch. Uzeir Mustaqfirin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
several products offered to prospective customers, one of which is its financing service product. In this financing service product, the contract used is the mudharabah contract, which in practice is much sought after by customers because the application requirements are easy and the disbursement of funds is quite fast. Due to the large number of customers and prospective customers who choose to use this financing service product, this has resulted in a significant increase in the number of customers at KJKS Artha Buana from year to year. This has an impact on the profits obtained by KJKS Artha Buana. The aim of this research is to determine the practice of mudharabah financing product contracts at KJKS Artha Buana and to find out an analysis of the implementation of mudharabah financing contracts at KJKS Artha Buana from a sharia economic law perspective. The type of research used is field research using a qualitative descriptive approach, collecting data through observation, interviews and documentation. The results of this research are the determination of profit sharing in mudharabah financing contracts carried out by KJKS Artha Buana using two systems, namely the flat system and the sliding system. This flat and sliding system is not in accordance with the financing theory using existing mudharabah contracts. And it is also not appropriate as stated in DSN fatwa Number 07/DSN-MUI/IV/2000 concerning Mudharabah (Qiradh) financing.